A component-based specification approach for embedded systems using FDTs. - Guerrouat, Abdelaziz (Software engineering notes.)
This paper presents a framework for specification and testing of component-based embedded systems using formal description techniques (FDTs). We deal with embedded systems from the point of view of communication and thus we propose a communication model for them. We further explain the meaning of component-based embedded systems and how these can be specified using FDTs. FDTs such as Estelle and SDL are based on EFSMs (Extended finite State Machines) and have been widely used in the automation of the development process of protocols and communicating systems, i.e. for specification, analysis and validation purposes. The main goal of this work is to demonstrate the reusability of FDTs for component-based systems.